2011
DOI: 10.1177/1545968311423668
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Effect on Voluntary and Stretch Reflex–Related Torque Produced by the Quadriceps

Abstract: BoNT A appeared to delay the stretch-reflex angle at peak torque, whereas the voluntary torque decreased. After strict patient selection, BoNT A injection into the RF muscle led to improvements in impairment, activity, and discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…Bernuz et al 26 reported that 3/15 participants had subsequent hip flexion weakness after injection of rectus femoris, despite no weakness in the knee extensors. Whether the weakness affected walking ability was not reported, and there was no subanalysis for whether outcomes were worse for these affected individuals.…”
Section: Adverse Events With Bont Injectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bernuz et al 26 reported that 3/15 participants had subsequent hip flexion weakness after injection of rectus femoris, despite no weakness in the knee extensors. Whether the weakness affected walking ability was not reported, and there was no subanalysis for whether outcomes were worse for these affected individuals.…”
Section: Adverse Events With Bont Injectionsmentioning
confidence: 99%
“…Most studies [26][27][28][29]31,33 also reported an improvement in functional outcome measures in the ICF activity domain. However, an improvement in MAS was not always associated with improvement in function; 8 of the 19 participants in the case series by Hecht et al 30 discontinued BoNT injections for this reason.…”
Section: Chemodenervation With Bontmentioning
confidence: 99%
See 3 more Smart Citations